2013
DOI: 10.1177/0192623313486316
|View full text |Cite
|
Sign up to set email alerts
|

Parenteral Solution of Nutritional Hepatotrophic Factors Improves Regeneration in Thioacetamide-induced Cirrhotic Livers after Partial Hepatectomy

Abstract: Liver resection is a suitable option for the treatment of certain hepatic conditions, particularly hepatocarcinomas, in patients with cirrhosis. However, this disease impairs liver regeneration, which increases the risk of liver failure and postoperative death. Supportive treatments for regeneration of the remaining liver may be useful for the recovery of these patients. We demonstrated that nutritional hepatotrophic factors (NHF) is an effective regenerative stimulus for cirrhotic livers in rats subjected to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
4

Year Published

2017
2017
2017
2017

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 50 publications
(90 reference statements)
0
1
0
4
Order By: Relevance
“…The proportion of binucleate to uninucleate hepatocytes was 13% in the control for the undernourished group; increased to 18% in the undernourished group -explained by the 90% increase in the number of binucleate hepatocytes; subsequently reduced to 10.4% in the renourished group explained by the 85% increase in the number of uninucleate hepatocytes; and finally reached 7.7% in the control for the renourished group. Similarly, very recently, it has been demonstrated that the administration of a proteinic parenteral solution of hepatotrophic factors in partially-hepatectomised rats led to a 44.9% rise in the hepatocyte proliferation rate increasing the liver regenerative capacity [35].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 88%
“…The proportion of binucleate to uninucleate hepatocytes was 13% in the control for the undernourished group; increased to 18% in the undernourished group -explained by the 90% increase in the number of binucleate hepatocytes; subsequently reduced to 10.4% in the renourished group explained by the 85% increase in the number of uninucleate hepatocytes; and finally reached 7.7% in the control for the renourished group. Similarly, very recently, it has been demonstrated that the administration of a proteinic parenteral solution of hepatotrophic factors in partially-hepatectomised rats led to a 44.9% rise in the hepatocyte proliferation rate increasing the liver regenerative capacity [35].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 88%
“…(Banks, 1992 (Brenner, 2009). O modelo que utiliza a TAA é o mais recente (Guerra et al, 2009, Cogliati et al, 2010, Trotta et al, 2013, produz alterações mais próximas às que ocorrem na cirrose humana (Laleman et al 2006) tais como a peroxidação das membranas lipídicas, necrose celular, fibrose e reorganização micronodular do parênquima, proliferação ductular (Sun et al, 2000) e, finalmente, cirrose macronodular (Hakateyama et al, 2002).…”
Section: O Fígadounclassified
“…A utilização deste modelo tem como objetivos a compreensão do desenvolvimento da cirrose e suas consequências, além de estratégias para a sua prevenção e tratamento farmacológico alopático ou com extratos vegetais e soluções nutricionais (Low et al, 2004;Nagata et al, 2005;Pinzani et al, 2005;Chen et al, 2006;Laleman et al, 2006Noda et al, 2006Guerra et al, 2009;Furtado et al 2012;Salama et al, 2012;Xie et al, 2012, Trotta et al, 2013.…”
Section: A B Cunclassified
See 2 more Smart Citations